Greenspace and intestinal diseases: a systematic review and meta-analysis - Ao Zhang; Tianyi Zhao; Hongyi Li; Tianyu Xia; Shijie Zhang; Yuxin Zhu; Kang Ding (BMC Public Health)
Abstract Greenspace has been reported potential therapeutically beneficial for intestinal diseases, yet the findings remain controversial Current researches demonstrate diversity in the assessment of greenspace and involve broad population groups, with the publication bias remaining a concern. This study offers convincing and reliable evidence supporting the beneficial effects of greenspace exposure on intestinal health, through a systematic review and meta-analysis examining the association between greenspace and intestinal disorders. The Greenspace exposure was primarily assessed using the Normalized Difference Vegetation Index (NDVI) and residential proximity to greenspaces. A comprehensive assessment was conducted concurrently by integrating various methods, such as land-use and satellite image data. This research encompassed a variety of intestinal conditions, such as inflammatory bowel disease (IBD), Crohn’s disease (CD), ulcerative colitis (UC), colorectal cancer (CRC), and diarrhea. A search was performed cross four English and two Chinese databases, yielding nine studies for systematic review and eight for meta-analysis from 11,497 identified records. The results illustrated a significant protective effect of greenspaces against CD and IBD as well as a potentially protective effect against diarrhea. Nonetheless, no significant association was detected for UC or CRC. The study established that greenspaces could influence intestinal health through potential mechanisms such as improved air quality, enhanced microbial diversity, and reduced stress. These findings provide a solid basis for developing healthier urban environments and advancing strategies for prevention and treatment of intestinal diseases. Trial registration Registration number: CRD42024625968.